Stock Market Increase and Decrease using Twitter Sentiment Analysis and ARIMA Model - Kedar, S. V. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With centuries and decades, people started evolving and slowly started entering into technology era. Social networks era came before everyone which connected people from far away countries. Such an example of social network are applications like Twitter, Facebook, Instagram, LinkedIn etc. Every application has its own significance. Such an application is Twitter where people tweet regarding their opinion about a topic, a person anything. The tweets regarding company its performance and people’s opinion about the stock is also tweeted. People like to invest in stocks using this data posted of social networking. This data keeps them updated about a company. In this paper, we will be using tweets related to stocks so that we can analyse sentiments of people regarding a particular stock. This sentiment analysis can provide a feedback about the company so that we will be able to understand an increase or decrease with respect to the people or company performance. In later stages, we will be comparing this analysis with ARIMA model which is time series forecasting model. ARIMA takes values of stocks and predicts its future prices based on its algorithm. Using both of these techniques a cumulative result for stock exchange will be obtained. The dataset is the fresh tweets taken from twitter and also the stock data will be imported directly for ARIMA.